2013
DOI: 10.5550/sgia.130902.en.007n
|View full text |Cite
|
Sign up to set email alerts
|

Training Effects on General and Specific Motor Skills on Female Volleyball Players 13-14 Years Old

Abstract: The physical growth and development of motor skills, are important components that can be programmed to act physical exercise and training. The aim of this study is to present the impact of volleyball training at changing the general and specific motor abilities at female volleyball players 13-14 years old. The sample represented 40 subjects, students at volleyball school "DIF" from Belgrade. In this study, the sample of variables is divided into two sub-samples (variable assessment of general motor skills and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Moreover, Nešič et al [23] showed certain improvements in the general and specific motor skills (volleyball skills) after three months of applied volleyball practice. Similar results were obtained in PE classes following a precisely defined volleyball program of techniques and tactics [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nešič et al [23] showed certain improvements in the general and specific motor skills (volleyball skills) after three months of applied volleyball practice. Similar results were obtained in PE classes following a precisely defined volleyball program of techniques and tactics [24].…”
Section: Discussionmentioning
confidence: 99%
“…The explosive force property exhibited by its muscles depending on the maximal force was measured (Bayraktar, 2010;Mackala et al, 2013). Standing broad jump (SBJ) measurements were conducted according to the Nešić' protocol (Nešić et al, 2013). Throwing medicine ball (THMB) is a test for assessment of explosiveness of the shoulder area (the results were obtained with an accuracy of 1 cm) (Nešić et al, 2013).…”
Section: Physical Fitness Testsmentioning
confidence: 99%
“…Standing broad jump (SBJ) measurements were conducted according to the Nešić' protocol (Nešić et al, 2013). Throwing medicine ball (THMB) is a test for assessment of explosiveness of the shoulder area (the results were obtained with an accuracy of 1 cm) (Nešić et al, 2013). Sit-ups (SU30s) tests were measured by bending the elbows from the straight position, then approaching the ground and straightening the elbows again.…”
Section: Physical Fitness Testsmentioning
confidence: 99%
“…Countermovement Jump (CMJ) was performed on a contact mat platform [9]. Standing Broad Jump (SBJ) and Standing Triple Jump (STJ) measurements were conducted according to the Nešić Protocol [10]. Standing medicine ball throw (SMBTH) is a test for assessment of explosiveness of the shoulder area (the results were obtained with an accuracy of 1 cm) [10].…”
Section: Participantsmentioning
confidence: 99%
“…Standing Broad Jump (SBJ) and Standing Triple Jump (STJ) measurements were conducted according to the Nešić Protocol [10]. Standing medicine ball throw (SMBTH) is a test for assessment of explosiveness of the shoulder area (the results were obtained with an accuracy of 1 cm) [10]. 10-meter and 20-meter sprint test measurements were performed according to the Bjelica and Fratrić protocols (the result is given with an accuracy of 0.1 sec) [11].…”
Section: Participantsmentioning
confidence: 99%